Adaptative Aspects of Hominization. Part II. Nutritive Adaptations - Kujawa, Betina (Anthropological Review, 1994)
An attempt to reconstruct the potential Australopithecines’ diet is based first of all on comparative analysis of their dentition and teeth of modern antropoids and the nutrishment they feed on. Study on dentition of Australopithecines suggests a great contribution of food characterizing by hard consistency (particularly in the case of massive forms, as A. robustus) but excludes a narrow specialization, whether in the carnivores’ direction or in the seed-eaters’ one. It seems that the atractiveness of the food in demand is composed of its high caloricness (seeds with high fat content) and fruits or young shoots with high sugar content) as well as the low concentration of toxical substances and the presence of compounds of phosphorus and exogenous amino acids (meat, bone marrow).